Turning back the tide of Indigenous language loss: Children to the rescue? - Kikkawa, D (Department of Social Services, 2015)
This article examines the prevalence of learning and use of Indigenous children in the Footprints in Time study.
Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 5
Keywords: Children -- Indigenous; Culture -- Culturally and Linguistically Diverse; Culture and language; Children; Culture; Culturally and Linguistically Diverse; Indigenous; Culture, identity and language; Culture and identity